Common responsibility in the 1990's : the Stockholm Initiative on Global Security and Governance, April 22 1991 - Stockholm Initiative on Global Security and Governance (Stockholm, Sweden : Prime Minister's Office, 1991)
This book deals with the unique opportunity to meet the global challenges ,securing peace, sustainable development and democracy.
oo 09/04/2019
Loans
Keywords: International relations; Security, International; Sustainable development